A Comparative Assessment of Knowledge and Awareness Regarding Breast Cancer among Women of Reproductive Age Group in District Etawah - Mahima Kumar; Dhiraj Kumar Srivastava; Pankaj Kumar Jain; Sandip Kumar; Anand Mohan Dixit; Ruchi Yadav (Medsci Publications, 2017)
Introduction: Late presentation has been observed as the hallmark of breast cancer, due to lack of awareness and non-existent breast cancer screening programmes. Breast cancer is the most common female cancer worldwide including India. The study was conducted to assess the awareness about breast cancer among the reproductive women and to find out the factors responsible for increased awareness. Methodology: A cross-sectional descriptive study was carried out among 250 reproductive age group females of rural and urban area of Etawah district. Information was collected under following broad headings:-Educational Status, socio-demographic profile and knowledge of various risk factors, preventive measures and screening. Result: Majority of the participants were illiterate (23%) and belong to upper lower (34%) and lower class (33%).Out of 250 participants 147(59%)were unaware about breast cancer. On comparing knowledge, rural females were more unaware about breast cancer, its warning symptoms, signs and its preventive measures. Also awareness of Self Breast Examination was very low in both urban and rural population. Conclusion: The present study hereby concludes that knowledge about breast cancer among reproductive females was low. In comparison to urban area this knowledge is very low in rural area.